Enzymatic debittering of Citrus reticulata (Kinnow) pulp residue and its utilization for the preparation of vermicelli. Issue 2 (12th December 2020) - Singla, Gisha; Panesar, Parmjit S.; Sangwan, Rajender S.; Krishania, Meena
Abstract: This study involves the debittering of Citrus reticulata (kinnow) pulp residue and its value addition through incorporation for the preparation of vermicelli. The optimization of debittering has been monitored through conversion of naringin (bitterness causing compound) to naringenin (nonbitter compound) through enzymatic method. The enzyme (naringinase) concentration has been varied from 0.5 to 2.5 U/mg with temperature range of 25–65°C at pH 4.5 with incubation period of 2–6 hr. The maximum reduction (~66.19%) naringin was observed in the kinnow pulp residue, with increase in the naringenin concentration (nonbitter) of 52.38% under optimized conditions, that is, enzyme concentration (1 U/mg), temperature (50°C), and treatment time (4  hr) at natural pH (4.5). The debittered kinnow pulp residue was characterized for compositional analysis and morphological studies using SEM and FTIR. The obtained debittered kinnow pulp residue was further successfully utilized in the preparation of nutrient and antioxidant‐rich vermicelli. Practical applications: Food waste has been generated in abundance by fruits processing industries which are rich in mineral, antioxidants, and polyphenols. The bitterness in citrus waste (kinnow pulp, peel, and seeds), has posed a major issue for their utilization in different food products due to the problem of consumer acceptability. In present investigation, reduction in the content of naringin below the threshold limit resulted in debittering of kinnow pulp residue. Furthermore, this debittered pulp residue has been explored for its utilization for the preparation of antioxidant rich vermicelli. Results of this work depicted that such technology can be used for debittering of kinnow industry by‐products and can be subsequently utilized by the food industry in the preparation of antioxidant rich food products. This process is not only an effective utilization of agro‐industrial by‐products/wastes but also solution for environmental waste caused by kinnow juice industry.